Avian Influenza: Hong Kong Outbreak - Gary D. Butcher; Richard D. Miles; Amir H. Nilipour (EDIS, 2005)
This document is VM138, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date June 12, 2002, reviewed and revised May 16, 2005.